Analisis Efektivitas dan Efisiensi Penggunaan Sistem Atlas dalam Proses Audit Laporan Keuangan - Anggita Shita Kusumawati; Agus Munandar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effectiveness and efficiency of using the Audit Tools and Linked Archive System (ATLAS) in the financial statement audit process at Public Accounting Firms (PAFs). A qualitative descriptive approach was employed, with data collected through interviews with auditors who had implemented ATLAS. The results reveal that ATLAS enhances audit effectiveness by integrating processes, standardizing working papers, and facilitating supervision. In terms of efficiency, ATLAS reduces audit completion time and lowers operational costs through digital documentation. The system also strengthens accountability through transparent audit trails. However, challenges such as limited IT infrastructure and resistance from senior auditors remain. Managerial support, continuous training, and technological readiness are crucial for successful implementation. Overall, ATLAS significantly contributes to improving auditor professionalism and promoting digital transformation in financial auditing practices.